1999
DOI: 10.1097/00003072-199907000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Differences in Hydration on Bone-to-Soft Tissue Ratios and Image Quality in Bone Scintigraphy

Abstract: This prospective study evaluated the effects of different amounts of fluid intake on the bone-to-soft tissue (B:ST) ratio and image quality of bone scans performed using Tc-99m MDP. One hundred sixty patients with no renal disease were divided into three groups with different degrees of hydration in liters (group 1, 0.25 I; group 2, 1 I; group 3, 1.5 I), and image quality was assessed with a semiquantitative score. The B:ST ratio was calculated over the femoral diaphysis and adductor area, respectively. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…() and Klementz et al . (); there was no improvement of bone soft‐tissue contrast and image quality in well‐hydrated patients which is in concordance with our study. Ferreira et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…() and Klementz et al . (); there was no improvement of bone soft‐tissue contrast and image quality in well‐hydrated patients which is in concordance with our study. Ferreira et al .…”
Section: Discussionsupporting
confidence: 92%
“…In this group, the hydration reduces the activity in the background and preserves it in the skeleton, which gives a comparable image quality with a reduced effective dose to the patient. In two published studies by Cronhjort et al (1997) and Klementz et al (1999); there was no improvement of bone soft-tissue contrast and image quality in well-hydrated patients which is in concordance with our study. Ferreira et al (2009) found, however, an improvement of bone-to-soft-tissue ratio in a published abstract.…”
Section: Bladder Activity Statistical Significancesupporting
confidence: 93%
See 1 more Smart Citation
“…Variation in this ratio is a well‐known dilemma and in practice, considerable deviations in image quality are accepted 5 . The B:S ratio increases with time post radiolabeled bisphosphonate administration due to increase the bone uptake and wash‐out of the extracellular activity through urinary excretion 6,7 . In humans, it has been estimated circa 34% of the 99m Tc‐diphosphonate 4 h post injection remains unbounded 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies reject this theory. 23,24 The renal function of the included horses was not assessed. For this reason, we cannot exclude subclinical renal dysfunction, which may influence the urinary extraction of 99m Tc-disphosphonates.…”
Section: Discussionmentioning
confidence: 99%